UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN KERTAS BERWARNA - Suyatmiati Suyatmiati (STKIP PGRI Tulungagung, 2019)
This research is aimed to improve mathematics students learning achievement inelementary school, especially inmixed count operation on integer materials through the application of colored paper learning media. This research was a classroom action research refferedto Kemmis and Mc Taggarts design, which includes planning, acting, observing, and reflecting. The research subject were all the student of fourth A gradeÂ in SDN Wadungsari Waru Sidoarjo inÂ theÂ the period of 2016/2017. Before the implementation of the action, the classical average value is 58.75. After the action is applied, the results of the test on cycle I is 75 for classical average value and the results of the test onÂ cycle II is 84,38 with student learning completeness